Pengaruh Kualitas Produk dan Customer Experience Terhadap Kepuasan Harga Dan Repurchase Intention Di RM Gubug Gurame Depok - Wisna; Meylani Tuti (LPPM Universitas Asa Indonesia, 2023)
This research aims to determine the influence of product quality and coustomer experience on price satisfaction and repurchase intention at Rm Gubug Gurame Depok. The population in this study was the coustomer Rm Gubug Gurame. The population in this study were customers of Rm Gubug Gurame Depok in June 2023. The research method used was a quqntitative method. The sampling technique used was purposive sampling. The sample in this study amounted to 140 people. This research uses data analysis techniques with SEM and uses SmartPLS. The results show that customer experience has a positive and significant influence on price satisfaction, coustomer experience has no direct influence on repurchase intention. Price satisfaction has positive and significant effect on repurchase intention. Product quality has a positive and significant influence on price satisfaction, whilw repurchase intention has direct influence.